2012
DOI: 10.4103/0973-1482.95193
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous bilateral medullary carcinoma of breast: Is it metastasis or second primary?

Abstract: Bilateral breast cancer is a rare event accounting for 2-5% of all breast malignancies. A second tumor in contralateral breast may be either synchronous or metachronous lesion. Synchronous bilateral invasive ductal carcinoma is known but medullary carcinoma is rare. The etiology of bilateral breast cancer is uncertain and prognosis in these cases once thought to be poor but recent data suggest a similar survival compared to unilateral disease. We report a case of triple negative synchronous bilateral medullary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 6 publications
2
11
0
Order By: Relevance
“…However, in our cohort, only 6.0% of the TMBC patients had a family history of breast cancer, indicating that the correlation between TMBC and the BRCA1 mutation remains to be determined. In 2012, Chandrika et al [28] reported a case of triple-negative synchronous bilateral medullary carcinoma, and a similar result was found in one of our patients who presented with two synchronous ipsilateral breast lesions which showed triple-negative disease.…”
Section: Discussionsupporting
confidence: 86%
“…However, in our cohort, only 6.0% of the TMBC patients had a family history of breast cancer, indicating that the correlation between TMBC and the BRCA1 mutation remains to be determined. In 2012, Chandrika et al [28] reported a case of triple-negative synchronous bilateral medullary carcinoma, and a similar result was found in one of our patients who presented with two synchronous ipsilateral breast lesions which showed triple-negative disease.…”
Section: Discussionsupporting
confidence: 86%
“…The second tumour in the contralateral breast can be either synchronous (within 6 months of the primary tumour) or metachronous (after 6 months of the primary). 2 In the present case, the second lump in the left axilla developed 4 months after the right breast lump. The exact etiology is not clearly defined (Chen et al) but among the various hypothesis suggesting risk factors for bilaterality of breast carcinomas; lobular carcinoma as the primary carcinoma is considered as an important factor.…”
Section: Discussionmentioning
confidence: 85%
“…Bilateral Breast Carcinoma (BBC) is an uncommon presentation with an incidence of 2-5% of all breast malignancies, Chandrika et al 1,2 Understanding the various factors contributing the development of contralateral tumour is important to ameliorate its altered clinical course, exaggerated treatment course and cost, aggravated prognosis as compared to unilateral tumour. Here is a case of a 56-year-old female with bilateral breast carcinoma with same histology and different grade on either side, who was managed adequately and recovered well.…”
Section: Introductionmentioning
confidence: 99%
“…Bilateral breast cancer has been reported from countries as diverse as USA, Italy, Greece, India, and Japan [1][2][3][4][5]. Therefore, the present paper documents the parameters discovered among the Igbo Ethnic Group, which is domiciled in South-Eastern Nigeria.…”
Section: Introductionmentioning
confidence: 90%